Über äolische Abtragung und Formung in der Südost-Sahara - Hagedorn, Horst (ERDKUNDE, 1968)
The Borkou mountain area in the south east Sahara lies on the south west edge of the geological Kufra Basin. The rocks of the mountain area are predominantly sandstones, deposited in succession from the Cambrian to the Cretaceous. The structural relief forms are therefore widespread structural terraces. The climate of the area is completely arid and is ruled by the NE trade wind, which blows from September to May with extraordinary regularity and strength. Relief is characterised by wind corrasion forms, which also take in the basal portion of the mountain area. Wind relief is described and analysed with the help of some air photos. The dominant forms are wind alleys and aerodynamically formed ridges stretching NE/SW and owing their formation to the grinding activity or the trade wind. The grinding material is quartz sand, which is irregularly distributed over the mountain area. The most important removal process is corrasion; deflation plays only a subordinate role. A series of relief levels is recognised and analysed with air photos, on the basis of surface forms from areas of varying altitude but with similar petrographie and tectonic composition. One level of aeolian formations below 600 metres is set against a fluvial formation above a boundary area at about 600 metres. The area of fluvial form type is characterised by gorge-like valleys. During the Quaternary the fluvial level more than once spread out to a lower level at the expense of the aeolian. This can be worked out through relict forms and corresponding humid-period sediments. The serial nature of the relief levels is the expression of a climatic-morphological state of affairs in the desert which divides according to altitudinal criteria. This can also be observed in other parts of the Sahara.